Regioselective deacetylation of peracetylated glycosides with a cleavable aglycone; Carbohydrate Research; Vol. 556 - Abramov P. A. Pavel Aleksandrovich; Fefelova A. G. Anastasiya Grigorievna; Shatskiy A. Andrey; Karkas M. D. Markus; Stepanova E. V. Elena Vladimirovna (2025, 2025)
Title screen